Challenges in Enforcing Surrogate Agreements and Surrogate Mothers in Indonesia - Muhamad Wahyudin; Zakaria Syafe’i; Muhammad Ishom (Faculty of Law, Universitas Pekalongan, 2025)
This study discusses the legal challenges in the practice of surrogacy in Indonesia from the perspective of positive law and maqāṣid syarī‘ah. The background to the issue stems from the increasing need of infertile couples for alternative reproductive technologies, while regulations in Indonesia still prohibit and have not comprehensively regulated this practice. Surrogacy is considered socially taboo and contrary to religious values, thereby creating a legal vacuum that poses risks to all parties, especially the child and the surrogate mother. The methodology used is a legal-normative and sociological approach, with the main theories being contract law, the principle of ijarah, and maqāṣid syarī‘ah. A comparison is made with Iran’s legal system, which regulates surrogacy through state-recognized contractual mechanisms, unlike Indonesia, which remains restrictive. The research findings indicate that the absence of explicit regulations in Indonesia creates legal uncertainty, opens the door to exploitation, and fails to guarantee the rights of children and surrogate mothers. Conversely, Iran has established strict yet clear legal and religious requirements, thereby providing legal certainty and better protection. The discussion addresses five research questions and demonstrates that the ban on surrogacy in Indonesia contradicts medical realities and societal needs. This study recommends a contract model based on maqāṣid syarī‘ah and the principle of ijarah, which is non-commercial in nature, to bridge the gap between positive legal requirements, religious values, and technological developments. In conclusion, Indonesia needs responsive, ethical, and religiously-based surrogacy regulations to prevent exploitation and ensure justice for all parties involved.